INNOVATIONS IN TRANSPLANTOLOGY: XENOTRANSPLANTATION AND ITS IMPACT ON THE HEALTHCARE SYSTEM AND SOCIETY - Justyna Bogdan; Benedykt Baljon; Izabela Harpula; Radosław Ramotowski; Paulina Frączkiewicz; Patryk Brzezicki; Natalia Bębenek; Gabriela Barszcz; Monika Błądek; Karolina Drygała; Sylwia Wit (International Journal of Innovative Technologies in Social Science, 2025)
According to statistics collected by organisations such as Eurotransplant and OPTN Transplant, there is a shortage of organs available for transplantation. The highest demand is for kidneys, with over 100 000 people on the waiting list. Xenotransplantation – inter-species transplantation – may be a solution to this problem. The initial attempts at transfusing animal blood date back to the 17th century. Scientists showed interest in this field not until early 20th century. To perform a pig-to-human kidney transplant while reducing the risk of complications, it is necessary to genetically modify the pig's DNA. Microinjections, viral vectors, or specialised proteins are used to remove animal-specific antigens, eliminate endogenous viruses, and make the animals’ cells more similar to human’s. The chances of success can be increased by administering immunosuppressive drug, preventing rejection. Animal tissues, such as pig’s corneas, are routinely used in medicine. Biological heart valves are also extracted from animals, strictly prepared and then implanted into hearts of individuals whose physiological valves have failed. Coming years may change the clinical implications of animals, as studies have already been published in which humans received complete animal organs such as kidneys, hearts, and livers. This subject, however, sparks a debate in society and raises ethical and religious dilemmas. The main concerns include zoonotic diseases and unequal access to xenotransplantation. Representatives of the world's major religions have not shown opposition, which, coupled with increasing public acceptance, may allow scientists to improve genetic modification techniques and standardise procedures to save lives in the future.